Dermatological Complications of COVID 19 Vaccines: An Updated Review - Alsadi, Mohammed Omar; John, Vinita (National Journal of Community Medicine, 2023)
Vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the 2019 coronavirus disease (COVID-19) pandemic, have been rapidly developed and authorized. However, recent studies showed that COVID-19 vaccination is associated with a wide range of dermatological reactions. The most prevalent adverse dermatological reaction observed in observational studies was a delayed large local reaction (DLRs), which is characterized by the appearance of an erythematous and edematous patch at the injection site four days or more after vaccination. Most of these reactions are common in females and resolve spontaneously within a few days to a weak. The second dose of the vaccine was associated with a higher incidence of cutaneous reactions compared to the first dose but milder in intensity. It seems that the Moderna vaccine is associated with a higher incidence of these adverse events compared to the Pfizer vaccine. Furthermore, mRNA vaccines had a higher incidence than vector-based and inactivated vaccines. There is a lack of evidence regarding the side events of the Johnson & Janssen vaccine. Further long-term, multicenter studies are required to compare these vaccines and highlight the best practice in managing these reactions.